2018
DOI: 10.3324/haematol.2017.183012
|View full text |Cite
|
Sign up to set email alerts
|

Competing-risk outcomes after hematopoietic stem cell transplantation from the perspective of time-dependent effects

Abstract: The success of hematopoietic stem cell transplantation is determined by multiple factors. Additional complexity is conferred by covariables showing time-dependent effects. We evaluated the effect of predictors on competing-risk outcomes after hematopoietic stem cell transplantation in a time-dependent manner. We analyzed 14951 outcomes of adult patients with hematologic malignancies who underwent a first allogeneic transplant. We extended the combined endpoints of disease-free and overall survival to competing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Time-dependent effects of other clinical covariates were also modeled and are shown in Table S1 in Supplemental Material. These time-dependent covariables resemble effects that were explored and published previously (24,27).…”
Section: Known Associations Of Non-permissive Hla-dpb1 Mismatches With Outcome Endpoints Confirmedmentioning
confidence: 91%
See 1 more Smart Citation
“…Time-dependent effects of other clinical covariates were also modeled and are shown in Table S1 in Supplemental Material. These time-dependent covariables resemble effects that were explored and published previously (24,27).…”
Section: Known Associations Of Non-permissive Hla-dpb1 Mismatches With Outcome Endpoints Confirmedmentioning
confidence: 91%
“…For the endpoints NRM, aGvHD and relapse, cumulative incidence curves for competing risk data were generated and compared with the method of Gray ( 23 ). For multivariate analyses cause specific Cox models have been used, allowing for adjustment of time-dependent covariate effects in a piecewise constant manner ( 24 ). The breakpoints were chosen graphically ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a study published in this issue of Haematologica, Fuerst and colleagues have added a fourth level of complexity: they hypothesized that the effect of different covariates may be different at different intervals from transplantation, and this is exactly what they found. 1 One example is the stem cell source: bone marrow and peripheral blood as sources of stem cells have been compared in numerous prospective and retrospective studies, including meta-analyses, to define which is better, and results have often been conflicting. Again the complexity of transplantation does not make comparisons easy: in the first randomized study 2 of patients with low-risk disease, receiving a myeloablative regimen and HLA identical sibling grafts, the hazard risk (HR) of death was 1.20 for recipients of peripheral blood compared to bone marrow (P=0.2).…”
mentioning
confidence: 99%
“…Fuerst and colleagues offer a new way of looking into this particular issue: they found that peripheral blood has a significant protective effect on non-relapse mortality early after transplantation, and a significant detrimental effect later on. 1 The time point for a change of effect on non-relapse mortality was set at 8 months: this means that patients receiving peripheral blood grafts had a lower non-relapse mortality within 8 months (HR: 0.75) and a higher non-relapse mortality beyond 8 months after transplantation (HR:1.38), which were both highly significant effects (Figure 1). There was no protective effect of peripheral blood on relapse, which is the competing event (Figure 1).…”
mentioning
confidence: 99%